Oblique wave scattering by a floating elastic plate over a porous bed in single and two-layer fluid systems. (1st July 2018) - Behera, H.; Ng, Chiu-On; Sahoo, T.
Abstract: An analytical study is presented in this paper for oblique wave scattering by a floating elastic plate in a one or two-layer body of water over a porous seabed of infinite depth. The solution procedure adopted, under the assumption of small-amplitude surface waves and structural response, is the eigenfunction expansion method. The study aims to look into the interaction between oblique waves and a floating elastic plate that serves as an effective breakwater. Effects of three types of edge conditions, viz. (i) free edge, (ii) simple-supported edge, and (iii) clamped edge are analyzed. Numerical results for the reflection and transmission coefficients are computed and examined for various values of the wave, porous bed and structural parameters. Results for wave interaction with an elastic plate over a non-porous bed are obtained as special cases and compared with results available in the literature. The study reveals that for various combinations of wave and structural parameters, zero reflection and full transmission may occur in case of rigid bottom and real porous-effect parameter of the porous bed. However, for complex porous-effect parameter, zero reflection and full transmission do not occur. Moreover, due to the energy dissipation by porous bed, wave transmission decreases significantly with increase in length of the floating plate in case of complex porous-effect parameter. The results will be useful in the design of breakwaters for the protection of harbors, inlets and beaches against attacks from surface waves. Highlights: Analytical model is developed for interaction between oblique waves and a floating elastic plate. Wave interaction is under the effects of a porous bed and a fluid with or without density stratification. Resistance-type bed condition is used. Analytical solutions are found using the eigenfunction expansion method. Results are discussed for various effects on the wave reflection by, and transmission through, the floating elastic plate.